25 Years of Politology of Religion - Miroljub Jevtić (Chrześcijaństwo-Świat-Polityka)
The increasing influence of religion in politics - a  fact which was suddenly noticed after the Iranian Islamic revolution, the role of religion in the downfall of the Warsaw Pact and socialist regimes in Eastern Europe, the resurgence of Hinduism by using the Bharatia Janata Party in India, the increasing importance of Judaism as a political ideology in Israel along with other examples from different religions, all together represented a challenge for political science. At the time, political science disciplines were not able to offer a solution for these questions. As a result, a specific political science discipline emerged, namely the Politology of Religion. This is a specific scientific discipline because of its specific research subject, separating it from other disciplines. Therefore, Politology of religion is both a general and a specific political science discipline. It is general because without its findings the education of a political scientist is not possible. On the other side, Politology of religion is a specific discipline due to its research of political science themes, in the context of religion. This discipline was firstly introduced as a course in the Department of Political Science of the University of Belgrade, in the school year 1993/1994. So far, hundreds of undergraduate political science students attended this course. Meanwhile, both Master and Specialist studies in Politology of Religion were developed. There is a Doctoral course as well. Therefore, the Department of Political Science of the University of Belgrade, educates politologists of religion from the undergraduate level, to the PhD level. The peak development of this discipline was, however, the first in the world publication of a journal in English dedicated to politics and religion – The Politics and Religion Journal (PRJ). PRJ gets its most valuable recognition from its authors, who come from all over the world. As such, PRJ is one of the most-multicultural social science Journal in the world